Increased Expression of CAP2 Indicates Poor Prognosis in Hepatocellular Carcinoma()() - Fu, Jia (Transl Oncol, 2015)
CAP2 has been suggested as a potential diagnostic biomarker for early hepatocellular carcinoma (HCC). However, its prognostic significance in HCC remains unclear. Here, we show that CAP2 expression is much higher in HCC tissues than that in paracarcinoma tissues, at both mRNA and protein levels. Data of immunohistochemistry (IHC) revealed that CAP2 was markedly up-regulated in 77.3% of HCC cases. High CAP2 expression, defined by the median score of IHC, was present in 53.3% of the patients. Kaplan-Meier analysis indicated that high CAP2 expression was associated with poor overall survival (P < .0001), disease-free survival (P = .013) and recurrence probability (P = .004) in a training cohort of 312 HCC patients. The prognostic implication of CAP2 in HCC was further confirmed in a validation cohort of 208 HCC patients and by stratified survival analysis. Multiple Cox regression analysis indicated CAP2 as an independent predictor for overall survival (hazard ratio (HR) = 1.615, 95% confidence interval: 1.345-1.938, P < .001). Collectively, we conclude that CAP2 is increased in HCC and is a novel unfavorable biomarker for prognostic prediction for patients with this deadly disease.